Legal mechanisms and the evolution of lists of critical and cross-cutting technologies in Russia within the context of the modern state’s technological sovereignty - Susha, Vladimir A.; Gavrish, Aleksandr N.; Kondratenko, Roman M. (Journal of the Belarusian State University. Law, 2026)
Based on a systematic analysis, the article examines the formation in Russia of a holistic legal model for ensuring technological sovereignty, which is considered an integral defining characteristic of the modern state. The key evidence supporting this thesis is the evolution of the lists of critical and cross-cutting technologies, which have transitioned from the first approved list (2002) to their current status of a core element of the technological sovereignty strategy (2023–2025). The main legal mechanisms for implementing this model have been identified and analysed: the conceptual division of technologies into critical and cross-cutting, the introduction of technology cooperation maps as the primary project tool, the establishment of a detailed system of expertise and planning, and the conditioning of funding on the step-by-step confirmation of technology readiness levels. A comparative analysis with the Belarusian model reveals structural differences and the potential for harmonising legislation within the Union State and the Eurasian Economic Union, which aligns with the shared strategic objective of strengthening technological sovereignty.
Keywords: technological sovereignty; critical technologies; cross-cutting technologies; technology policy; legal regulation; technology cooperation maps; technology readiness level; Union State; Eurasian Economic Union